2022
DOI: 10.3389/fpubh.2022.1071229
|View full text |Cite
|
Sign up to set email alerts
|

Influenza incidence and air pollution: Findings from a four-year surveillance study of prefecture-level cities in China

Abstract: BackgroundInfluenza is a serious public health problem, and its prevalence and spread show significant spatiotemporal characteristics. Previous studies have found that air pollutants are linked to an increased risk of influenza. However, the mechanism of influence and the degree of their association have not been determined. This study aimed to determine the influence of the air environment on the spatiotemporal distribution of influenza.MethodsThe kernel density estimation and Getis-Ord Gi* statistic were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…However, Li et al ( 10 ) did not observe a significant relationship between every 0.1 ug/m 3 increment of CO and influenza, which might be related to regional differences and population specificity. When CO enters the human respiratory tract, CO will form a competitive relationship with O 2 , which will prevent the delivery of oxygen in the body, thus reducing the resistance to influenza virus ( 6 ). However, when we pooled the results of all included original studies and did not stratify by the change in pollutant concentration, the significant association between CO and influenza risk disappeared.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Li et al ( 10 ) did not observe a significant relationship between every 0.1 ug/m 3 increment of CO and influenza, which might be related to regional differences and population specificity. When CO enters the human respiratory tract, CO will form a competitive relationship with O 2 , which will prevent the delivery of oxygen in the body, thus reducing the resistance to influenza virus ( 6 ). However, when we pooled the results of all included original studies and did not stratify by the change in pollutant concentration, the significant association between CO and influenza risk disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollutants have become an important global public health issue, in recent years, and a large amount of epidemiological and clinical evidence has shown that air pollutants are associated with respiratory diseases, and their adverse health effects have been well documented ( 5 ). Both brief and prolonged exposure to air pollution raises the risk of morbidity and death from a range of systemic illnesses, which can result in the emergence and spread of influenza ( 6 ). Air pollution can increase the incidence risk of influenza, including diagnosis cases ( 7 ) and outpatient visits ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, hot spots refer to areas with significantly high values that are surrounded by postal code regions with high values. This method was developed by Luc Anselin 46 and, among others, applied in the context of air pollution 16 , 47 . Several statistics represent the measure of spatial autocorrelation 48 , 49 .…”
Section: Methodsmentioning
confidence: 99%
“…Most individuals residing in Germany inhabit polluted regions 14 . Air pollution negatively impacts virus-transmitting infections such as influenza 15 , 16 and COVID-19 17 19 . Irrespective of which specific health outcome is considered, understanding the interdependencies between environmental variables and the selection of environmental stressors is a key aspect in epidemiological analyses.…”
Section: Introductionmentioning
confidence: 99%